2018
DOI: 10.29252/ibj.22.4.231
|View full text |Cite
|
Sign up to set email alerts
|

An Association Study between Longitudinal Changes of Leukocyte Telomere and the Risk of Azoospermia in a Population of Iranian Infertile Men

Abstract: Background: Telomeres are evolutionary, specialized terminal structures at the ends of eukaryotic chromosomes containing TTAGGG repeats in human. Several human diseases have been known to be associated with dramatic changes in telomere length. The aim of the present study was to assess the correlation between the relative leukocyte telomere length (LTL) and infertility in a group of Iranian azoospermic males. Methods: In this casecontrol pilot study, relative telomere length (RTL) of peripheral blood leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Regarding TL in leukocytes, three studies reported lower leukocyte TL in infertile patients than in fertile men 24,28,36 . Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Regarding TL in leukocytes, three studies reported lower leukocyte TL in infertile patients than in fertile men 24,28,36 . Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 .…”
Section: Resultsmentioning
confidence: 74%
“…Regarding TL in leukocytes, three studies reported lower leukocyte TL in infertile patients than in fertile men. 24,28,36 Similarly, longer leukocyte TL in 10 fertile men than in 10 oligozoospermic patients was reported by Amirzadegan et al 25 On the other hand, Yang et al 37 reported shorter leukocyte TL in 349 nonobstructive azoospermia patients than in 247 obstructive azoospermia patients and 270 normospermic men, and results from the Tahamtan et al 30 study showed significantly lower leukocyte TL in men with infertility resulting from varicocoele than fertile controls. Only two studies found no differences in leukocyte TL between normozoospermic and oligozoospermic men 14 or between fertile and infertile subjects.…”
Section: Differences In Leukocyte Tl Between Fertile and Infertile Or...mentioning
confidence: 66%
“…A positive association between male infertility factors and TL was observed in 19 studies (68-86) and a negative association in 2 studies (39,87) (Table II). In total, 15 of the positively associated studies detected a sperm TL (STL) association (68-70,72,74-84), while 3 studies detected an LTL association (73,85,86), and one study detected both STL and LTL (71). In several studies, shorter STL was reported in association to infertility (72,76,78,80) while Vecoli et al reported an increase in STL in areas of high environmental exposure (77).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 93%
“…Moreover, samples that were used for IVF and had abnormal STLs did not produce a successful pregnancy, whereas samples that had STLs within the normal range had a 35.7% success rate (79). Likewise, males with azoospermia exhibited a shortened STL (69,70), as well as a shorter LTL (85,86).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 99%
“…Infertility is characterized by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse (Vander Borght and Wyns 2018). Approximately one-half of infertility can be due to male-related factors or in combination with femalerelated fertility disorders (Heidary et al 2018). Male infertility usually occurs because of low sperm count or oligospermia, poor sperm motility, and morphological abnormalities (Hwang et al 2010).…”
Section: Introductionmentioning
confidence: 99%